Changes in muscle biochemistry, myoglobin and cytoglobin in goldfish Carassius auratus exposed to hypoxia-reoxygenation and microcystin RR. Issue 1 (2nd January 2016) - Okogwu, Okechukwu
Abstract: Cyanobacterial toxins and oxygen depletion pose serious challenges to aquatic organisms. In this study, the goldfish Carassius auratus was exposed to hypoxia-reoxygenation episodes as well as a cyanobacterial toxin microcystin arginine arginine (MCRR) with an aim of assessing the toxicity of the stressors to muscle biochemistry, cytoglobin mRNA and myoglobin mRNA. The result showed that MCRR and hypoxia-reoxygenation synergistically reduced the total antioxidant capacity of the muscle by over 90%; glutathione peroxidase activity was also significantly reduced in the groups exposed to MCRR and hypoxia ( p  < 0.05). Sodium ATPase (Na-ATPase) and total ATPase (tATPase) varied from 14.68 ± 2.2 to 27.87 ± 2.0 U/mg protein and were significantly reduced by MCRR ( p  < 0.005) only. Glucose and protein (sources of energy) were elevated in the muscles of goldfish exposed to MCRR, especially during reoxygenation, although only the latter was significant. Myoglobin and cytoglobin mRNA were not significantly influenced by hypoxia-reoxygenation, MCRR and both of them. Therefore, the combined effect of MCRR and hypoxia reduced the defense mechanism of the fish and accelerated the consumption of energy, which could compromise the survival of the goldfish during prolonged hypoxia episodes.